2013
DOI: 10.1158/1535-7163.mct-12-0273
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-100 Inhibits Human Bladder Urothelial Carcinogenesis by Directly Targeting mTOR

Abstract: miRNAs are involved in cancer development and progression, acting as tumor suppressors or oncogenes. In this study, miRNA profiling was conducted on 10 paired bladder cancer tissues using 20 GeneChip miRNA Array, and 10 differentially expressed miRNAs were identified in bladder cancer and adjacent noncancerous tissues of any disease stage/grade. After being validated on expanded cohort of 67 paired bladder cancer tissues and 10 human bladder cancer cell lines by quantitative real-time PCR (qRT-PCR), it was fou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 49 publications
7
72
0
3
Order By: Relevance
“…MiR-100 has been shown its tumorsuppressor functions in several cancers including ovarian cancer (Nagaraja et al, 2010), bladder cancer (Xu et al, 2013), hepatocellular carcinoma (Chen et al, 2013), cutaneous squamous cell carcinoma (Henson et al, 2009) and lung cancer (Liu et al, 2012). A recent miRNA array analysis described that miR-100 was down regulated in chondrosarcoma cells, indicating miR-100 might act as a tumor suppressor in human chondrosarcoma (Yoshitaka et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-100 has been shown its tumorsuppressor functions in several cancers including ovarian cancer (Nagaraja et al, 2010), bladder cancer (Xu et al, 2013), hepatocellular carcinoma (Chen et al, 2013), cutaneous squamous cell carcinoma (Henson et al, 2009) and lung cancer (Liu et al, 2012). A recent miRNA array analysis described that miR-100 was down regulated in chondrosarcoma cells, indicating miR-100 might act as a tumor suppressor in human chondrosarcoma (Yoshitaka et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Hundreds of miRNAs have been well-studied to regulate gene expression and play essential roles in a variety of biological processes including proliferation, differentiation, migration, cell cycle, and apoptosis (Croce et al, 2009;Ameres et al, 2013). It has been reported that miRNAs are involved in drug resistance (Zheng et al, 2010), and acting as potential oncogenes or tumor suppressors (Ma et al, 2010;Xu et al, 2013). MiR-100 has been reported play a tumor suppressor role through multiple pathways.…”
Section: Microrna-100 Resensitizes Resistant Chondrosarcoma Cells To mentioning
confidence: 99%
“…As shown in Figure 2D, the 3′-UTR of mTOR contains putative miR-100 complementary sites and the mirSVR score is -1.1698 and the PhastCons score is 0.6882. Besides, several studies 22,23 illuminated that miR-100-5p can regulate the expression of mTOR by directly binding to the 3′-UTR of mTOR by the luciferase reporter.…”
Section: Mirna Profiles Of A549 and A549/ddp And Their Correspondingmentioning
confidence: 99%
“…Their study demonstrated the effects of miR-100 on cell growth rates and clonogenicity capacity in the 5637 cell line, emphasizing a possible effect of this miRNA on bladder carcinoma pathogenesis. Xu et al (2013) found that the mTOR gene was a direct target of miR-100. siRNA-mediated mTOR knockdown phenocopied the effect of miR-100 in bladder cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Both mTOR and p70S6K (downstream messenger) presented higher expression levels in distant metastatic foci such as in liver and kidney metastases than in the primary tumor. Taken together, miR-100 may act as a tumor suppressor in bladder cancer, and reintroduction of this mature miRNA into tumor tissue may prove to be a therapeutic strategy by reducing the expression of target genes (Xu et al, 2013). However, the clinical significance and prognostic value of miR-100 in bladder cancer have not been investigated.…”
Section: Discussionmentioning
confidence: 99%